2021
DOI: 10.1177/02698811211032466
|View full text |Cite
|
Sign up to set email alerts
|

The dosing procedure that “makes the poison”: Comparing the effects of single versus cumulative alcohol administration methods on emotion recognition

Abstract: Background: Most people often consume alcohol cumulatively and gradually. Yet almost scientific knowledge about alcohol’s acute effects on cognition, behavior, and affect stems from laboratory studies that employ a single beverage administration procedure. Objective: This study tests the hypothesis that alcohol’s acute effects depend on both methods of administration and alcohol blood level. We introduce a new laboratory procedure for studying cumulative alcohol drinking and examine alcohol’s effects on emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…Two studies found the opposite effect, such that happiness recognition significantly worsened following a moderate 57 and a high 53 (Study 1) dosage of alcohol compared to placebo. One article 53 (Study 2) reported on a second study that used a cumulative drinking design. When comparing results across studies (i.e., single dosage procedure vs. cumulative dosage procedure), they found that participants who consumed a single high dosage of alcohol were significantly less accurate on happiness recognition than participants assigned to the cumulative drinking procedure who eventually drank to a high dosage of alcohol 53 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies found the opposite effect, such that happiness recognition significantly worsened following a moderate 57 and a high 53 (Study 1) dosage of alcohol compared to placebo. One article 53 (Study 2) reported on a second study that used a cumulative drinking design. When comparing results across studies (i.e., single dosage procedure vs. cumulative dosage procedure), they found that participants who consumed a single high dosage of alcohol were significantly less accurate on happiness recognition than participants assigned to the cumulative drinking procedure who eventually drank to a high dosage of alcohol 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Although both studies found impairments to negative emotion recognition, one of these two studies found a high dosage of alcohol‐impaired recognition of anger and disgust/contempt (and not sadness or fear), 40 whereas the second study found a high dosage of alcohol‐impaired recognition of fear (and not sadness or anger) 53 (Study 1) (see Supplemental Tables 1 and 2). Finally, five of the 16 studies that examined negative emotion recognition included low dosages of alcohol, with all five studies finding no effects of a low dosage of alcohol on negative emotion recognition 16,29,30,36 , 53 . (Study 1) Taken together, there do not appear to be consistent dose–response effects of alcohol on emotion recognition for positive or negative emotion recognition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations